Adoption of a tool to measure the extent of presence of social constructivism in high school and college physics classrooms - Malayao, Sotero O. Jr (Transactions of the National Academy of Science and Technology, 2011)
The move towards constructivism in classrooms have been widely initiated although not explicitly named as constructivism. In the early 1990's, DepEd together with DOST initiated programs to foster new approaches in teaching sciences and mathematics. Lately, with the rapid expansion of the capacity of computer, the ICT integration is becoming a widespread phenomenon and many other pedagogical innovations that are inherently or implicitly associated with ICT integration come into clearer focus. All these are manifestations of the immense scope of social constructivist perspectives in the learning process. However, measurement of the presence of the social constructivism is not being given due importance unlike in the neighboring countries. In this study, the Social Constructivist Learning Environment Survey (SCLES) made by Australian educators is being attempted for full adoption in physics classrooms both in high school and college. With the involvement of 1000 college students in MSU-IIT and 1,194 senior students throughout Mindanao, the reliability of SCLES was established. In the original study, the cronbach alpha in 5 different dimensions of SCLES ranged from 0.54-0.81 while the present study ranged from 0.55-0.72. The present study, however, showed an overall cronbach alpha of 0.82 which ws not established in the original study. The study further revealed that at its initial result, the SCLES can be a good measuring tool in investigating the extent of social constructivism in physics classrooms